Intersector element partitioning in tourmaline: a potentially powerful single crystal thermometer - van Hinsberg, V; Schumacher, J (2007)
Hourglass sector zoning, and related polar overgrowths, are common features of metamorphic tourmaline, developing as a result of variations in element preference on the different growth surfaces. For sector-zoned crystals, three domains are present for each growth zone (c+, c- and a), with compositional differences most distinct for Ca and Ti, and among c+ and c- sectors. Intersector differences vary, commonly showing decreasing fractionation from core to rim attributed to increasing metamorphic grade. Here we show that intersector element partitioning is temperature dependent and derive empirical geothermometers based on c+-c- and c+-a partitioning of Ca and Ti. These thermometers are applicable over a range of temperatures and bulk-rock compositions. Intersector partitioning is not affected by re-equilibration and records and preserves complete T-histories of individual tourmaline grains from prograde to peak and on to retrograde growth. Information on element mobility is preserved by tourmaline composition, because intersector partitioning is independent of element concentration. These factors make intersector partitioning an ideal tool to elucidate the thermal history of tourmaline grains and thus their host environment and tourmaline's refractory nature preserves these signatures even into the sedimentary record. © Springer-Verlag 2006.